Extracellular matrix protein 1 gene rs3737240 single nucleotide polymorphism is associated with ulcerative colitis in Turkish patients - Adalı, Gupse; Ersoy Tunalı, Nagehan; Yorulmaz, Elif; Tiryakioğlu, Necip Ozan; Güray Mungan, Sibel; Ulaşoğlu, Celal; Yılmaz Enç, Feruze; Tuncer, İlyas (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Ulcerative colitis (UC) and Crohn’s disease are chronic inflammatory diseases. Genetic, immunologic, and microbial factors play an important role in their pathogenesis. Extracellular matrix protein 1 (ECM1), a gene related to mucosal barrier function, has been shown to be associated with UC. This study aims to determine the relationship between ECM1 gene rs3737240 single nucleotide polymorphism (SNP) and UC in a group of Turkish patients. Materials and Methods: Ninety-four UC patients and 120 healthy controls were enrolled in the study. ECM1 gene rs3737240 SNP genotyping was performed using the polymerase chain reaction-restriction fragment length polymorphism method. Results: TT genotype was significantly more common in UC patients than in the healthy control group [p=0.034; odds ratio (OR) 2.34; 95% confidence interval (CI) 1.04-5.25]. The presence of C allele significantly lowered the UC risk (p=0.034; OR 0.42; 95% CI 0.19-0.95). TT genotype was significantly associated with azathioprine use in UC patients (p=0.037; OR 3.0; 95% CI 1.04-8.65). The C allele significantly reduced the probability of azathioprine use in UC patients (p=0.037; OR 0.33 CI 95% 0.11-0.96). No relation was found between rs3737240 SNP genotype and the phenotypical characteristics of UC patients. Conclusion: The TT genotype of ECM1 gene rs3737240 SNP significantly increased susceptibility for UC and azathioprine use in UC patients in a Turkish population. Cite this article as: Adalı G, Tunalı NE, Yorulmaz E, et al. Extracellular matrix protein 1 gene rs3737240 single nucleotide polymorphism is associated with ulcerative colitis in Turkish patients. Turk J Gastroenterol 2017; 28: 254-9.